The Culture of “Hijabers” Top Class in Social Media: Counter Hegemony or Next Hegemony? (Netnographic Study on the Instagram Accounts of Dian Pelangi and Dato' Seri Vida) - Rahman, Khairul Arief (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2023)
This article will discuss how Muslim women currently support their Islamic views through clothing that has been constructed in such a way. One of them is the phenomenon of "hijabers" among high-ranking Muslims as if confirming a new identity that is considered Muslim but still "current". Mastery in this discussion refers to a number of artists or public figures who also share their style and fashion via social media to fans. Making this kind of domination of upper-middle class Muslims over other class Muslim women. However, on the one hand, the use of the hijab as part of eastern culture is actually gaining ground again in line with people's desire to be religious but still trendy. So the hegemony that occurs can be said to be without coercion and is a necessity. However, on the other hand, this mastery is also a serious problem to be observed because the stigma that appears appears to be too luxurious and excessive due to the addition of "wow" accessories and the Western elements that are tried to be included.